Efek Motivasi Investasi Sebagai Moderator Pengaruh Pengetahuan Investasi Dan Perilaku Keuangan Terhadap Minat Investasi - Nesia, Satya; Widayati, Irin (Jurnal Pendidikan Akuntansi (JPAK), 2022)
The development of investment in Indonesia has increased during the post-Covid 19 economic recovery period. The public is realizing the importance of investing and the benefits, including students are also aware of this. The factors that encourage students to invest are investment knowledge, financial behavior, and investment motivation. This study aim's to investigate the effect of investment motivation as a moderator of the influence of investment knowledge and finance behavior. The population used is 2015-2019 accounting education students who are still students with a total of 145 students. The sample used in the study was determined by the solving formula. While the sampling technique used is proportionate stratified random sampling. Data collection was carried out online in the form of a questionnaire in the form of a Google form. Then the data were analyzed using descriptive statistical methods then hypothesis testing was carried out using multiple linear regression analysis and moderation regression analyst the application used was SPSS version 26. Obtained from the results of the analysis of investment knowledge and financial behavior were able to produce a positive and significant influence on investment interest. Then investment motivation can moderate the effect of investment knowledge on investment interest.